Tetrapyrgos chukeatirotei (Agaricales, Marasmiaceae), a novel species from Yunnan Province, China - Bunphan, Jedsada; Zheng, De-Ge; Lu, Wen-Hua; Han, Mei-Yan; Pitakpattanakul, Chutimaphon; Chia, Poosanisa; Dai, Dong-Qing; Tibpromma, Saowaluck; Karunarathna, Samantha C. (Phytotaxa, 2025)
During an investigation of macrofungi in Yunnan Province, China, fruiting bodies of an interesting Tetrapyrgos species were collected growing on a piece of dead wood. This species is described and introduced as a new taxon (T. chukeatirotei), based on evidence from morphological and phylogenetic analysis of the nrITS sequence data. The new species is characterized by a hemispherical pileus, a pruinose surface with a brown center, greyish-yellow at the edges, and a pastel grey hue; the stipe is tapered downward and has a densely pruinose surface, which distinguishes it from other known species. A full description, illustrations, and phylogenetic analysis results of the new species, along with morphological comparisons to other species within this genus.